Designing telehealth for an aging population : a human factors perspective - Charness, Neil (Human factors & aging series, 2012)
"As simple and straightforward as two health professionals conferring over the telephone or as complex and sophisticated as robotic surgery between facilities at different ends of the globe, telehealth is an increasingly frequent component in healthcare. A primer on the human factors issues that can influence how older adults interact with telehealth systems, Designing Telehealth for an Aging Population: A Human Factors Perspective examines the new ways patients and healthcare providers communicate to achieve the same or better outcomes than with traditional face-to-face healthcare.The authors examine older adult capabilities and provide standards and guidelines for telehealth design, enlivened by clinical examples and tutorials on human factors methodologies. They take a systematic look at how the use of human factors principles can facilitate the successful development, deployment, and maintenance of telehealth technology to better serve the aging population. The authors have carefully stayed away from academic writing, distilling their experience in the form of basic observations and principles drawn from their work. They include suggested readings at the end of each chapter that supply the research underpinning their recommendations. The first reference to cover older adult users in an area that will only get bigger, this book sets itself apart by providing focused coverage of the human factors issues specific to aging populations and practical advice on how to accommodate them"--